Paternal involvement in a group of fathers of elementary school children - Simões, Rita Maria Correia da Silva (2011)
The purpose of this study was to evaluate the degree of paternal involvement in Portuguese parents of children between 5 and 9 years old, exploring factors of interindividual variability (father´s age, education, socioeconomic status and number of children), as well as the association between father involvement and a number of factors identified in the literature: parental satisfaction, parental stress and marital adjustment. The sample consists of 145 married fathers aged between 28 and 59 years (M = 40.14), most of them with a high and college degree of education and a middle socioeconomic status. Data collection was based on self-report assessment scales, along with a questionnaire for socio-demographic characterization. The main results point to a relatively high degree of paternal involvement, particularly in the dimensions Care and Availability, although in relative terms the father’s reports indicate a higher percentage of time given to mothers as primary caregivers of children. There were no significant differences between the fathers depending on the individual variables studied. However, we found a moderate negative association between father involvement and parental stress, and also a moderate positive association between father involvement and dyadic adjustment, which is consistent with other studies in this area. The results support the multidimensional conceptualization of father involvement, suggesting different dimensions of paternal behavior in relation to the care and education of children. In addition, the study confirms the multi-determined nature of paternal involvement, suggesting that personal and relational factors may have an impact on how men perform paternity. ------ RESUMO ------ O estudo pretendeu avaliar o grau de envolvimento paterno de pais Portugueses de crianças entre os 5 e os 9 anos de idade, explorando factores de variabilidade interindividual (idade do pai, educação, nível socioeconómico e número de filhos), bem como a associação entre envolvimento paterno e alguns factores identificados na literatura: satisfação parental, stress parental e ajustamento conjugal.A amostra é constituída por 145 pais casados, com idades entre os 28 e os 59 anos(M=40,14), a maioria dos quais com um nível de escolaridade secundário e superior e um nível socioeconómico médio. A recolha de dados foi realizada através da aplicação de questionários de auto-resposta, juntamente com um questionário para caracterização sócio-demográfica. Os principais resultados mostram um grau relativamente elevado de envolvimento paterno, sobretudo nas dimensões Cuidados e Disponibilidade, embora em termos relativos os pais atribuam às mães uma maior percentagem de tempo como principais figuras cuidadoras da criança. Não foram encontradas diferenças significativas entre os pais em função das variáveis individuais estudadas. Contudo, foi encontrada uma associação negativa moderada entre o envolvimento paterno e o stress parental, bem como uma associação positiva igualmente moderada entre o envolvimento e o ajustamento diádico, o que vai ao encontro de outros estudos realizados nesta área. Estes resultados suportam a conceptualização multidimensional do envolvimento paterno, sugerindo diferentes dimensões de comportamento paterno face aos cuidados e educação das crianças.Adicionalmente, confirmam a natureza multideterminada do envolvimento, sugerindo que factores pessoais e relacionais podem ter impacto na forma como os homens desempenham a paternidade.